The Multi Business Model Innovation Approach : Part 1. - Lindgren, Peter. (River Publishers, 2018)
The book addresses and documents a gap in BM research and the BM community - but also proposes a generic definition and language of a BM and BMI layers. The significance and importance of this work is related to significant and unexplored possibilities that BMI offers today, and can offer tomorrow.